Motivasi Penerapan E-Commerce Dalam Membangun Minat Berwirausaha Siswa di SMK Negeri 6 Tanjung Balai - Ahmad Muhazir; Arridha Zikra Syah; Yessica Siagian; Jeperson Hutahaean (Journal of Social Responsibility Projects by Higher Education Forum, 2021)
Entrepreneurial education and entrepreneurial characteristics have a positive influence on entrepreneurial motives. Therefore, the motivation is very suitable given at school age. Children of school age who have an entrepreneurial education background are one of them is in SMK Negri 6 Tanjung Balai which has a Marketing Department. So this kind of motivation is suitable for students who have the jurasan. Motivational ways are: Providing an understanding of Technopreneurship and Entrepreneurship, Providing motivation about starting entrepreneurial activities in accordance with good entrepreneurial characteristics, Explaining about e-commerce in an effort to deepen technopreneurship, Explaining the virtues of e-commerce applications and tools so as to help budding business people by using several examples. Community service activities at SMK Negeri 6 Tanjung Balai students have been completed at THE 6 Tanjung Balai State Vocational Hall with the topic of Motivation for The Implementation of E-Commerce in Building Entrepreneurial Interests of SMK Negeri 6 Tanjung Balai Students in the Era of Industrial Revolution 4.0 on September 5-6, 2019 and attended by students of smk negeri 6 TanjungBalai Business Department as many as 37 people